Cyber laws and it-rich society - P.S. Sangal, (Fakulti Undang - Undang, 2001)

(untitled)
Tremendous advances in technology have made big changes in the outlook of the people. Of all the technologies, Computer and Internet technologies, also called the Information Technology (in short IT), have grown and are still growing at the fastest pace. IT has given to mankind such a potent tool, which the mankind can use in doing possibly everything, except of course to control death. We are already using IT in industry’, commerce (e-commerce), education, entertainment, health (telemedicine), online advertising, creating virtual communities, flying aero planes, spying on others, fighting wars and what not